2012
DOI: 10.1021/ma300461d
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Small-Angle X-ray Scattering Study of Structure of Polymer Micelles Having Bromines in Hydrophobic Core

Abstract: Anomalous small-angle X-ray scattering (ASAXS) near the absorption edge of bromine has been used to investigate the internal structure of polymer micelles comprising poly(4-bromostyrene)-block-poly(ethylene glycol)block-poly(4-bromostyrene) (PBrS-b-PEG-b-PBrS) in aqueous solution. The ASAXS analysis revealed that the hydrophobic core composed of PBrS can be regarded as a homogeneous sphere with a radius of 10.2 nm and a decaying electron density at the surface. The aggregation number of micelle directly estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…ASAXS analyses have been applied for visualization of spatial distribution of a targeted element in nano-sized particles, such as metal nanoparticles, polymer micelles, and so forth [10][11][12][13][14][15][16][17][18][19][20][21][22]. Therefore, by using ASAXS for polymer micelles incorporating model drug compounds labeled with a marker element, we expect to visualize the 4 spatial distributions of drug compounds in polymer micelles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ASAXS analyses have been applied for visualization of spatial distribution of a targeted element in nano-sized particles, such as metal nanoparticles, polymer micelles, and so forth [10][11][12][13][14][15][16][17][18][19][20][21][22]. Therefore, by using ASAXS for polymer micelles incorporating model drug compounds labeled with a marker element, we expect to visualize the 4 spatial distributions of drug compounds in polymer micelles.…”
Section: Introductionmentioning
confidence: 99%
“…As written below, I(q) must be compared for the same value of q in ASAXS analyses, although the change in energy of incident X-ray led to a shift in the q-value assigned to a given pixel of the detector. Then, the SAXS profiles were interpolated by means of a cubic-spline method without any smoothing or corrections to correct for the q-shift [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…As an interesting example of physical accumulation, condensation of counterions onto micellar surfaces has been studied . As for chemical accumulation, so‐called tagged polymers were used where, for example, bromine atoms were chemically bonded to the targeted parts in a polymer chain, being applied to structural analyses of polymeric micelles having a core–shell interface with hydrophobic core …”
Section: Anomalous Saxsmentioning
confidence: 99%
“…where F 0 2 (q) is the non-resonant form factor, which can be measured by conventional SAXS, V 2 (q) corresponds to the form factor of the resonantly scattering parts, and the second term is the cross term of the resonant and non-resonant terms. The V 2 (q) factor can be obtained by numerically solving the simultaneous equations of Pðq; EÞ measured for at least three different energies near the K edge of a focused element (Akiba et al, 2012;Goergk et al, 2004;Patel et al, 2004):…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…For polymer systems, ASAXS using the K edge of Br is expected to be useful because Br atoms as ASAXS markers can be easily introduced into hydrophobic organic molecules through C-Br covalent bonds and the K edge of Br is within the range of energy of general synchrotron light sources (Akiba et al, 2012;Sakou et al, 2011;Varga et al, 2006Varga et al, , 2010. In a previous study, we used ASAXS analysis near the Br K edge to investigate polymer micelles (Akiba et al, 2012;Sakou et al, 2011). We found that the scattering profile of the hydrophobic core could be extracted from that of whole micelles by localizing Br in the core.…”
Section: Introductionmentioning
confidence: 99%